Response of durum and aestivum wheat varieties to nutrient management under late sown condition - Jhajhara, Gayatree; Sonalki, N.S.; Mundra, S.L.; Shukla, K.B. (Annals of Agricultural Research, 2018)
A field experiment was conducted at Rajasthan College of Agriculture, Udaipur, Rajasthan during rabi 2014-15 to assess the performance of durum and aestivum wheat varieties and nutrient management under late sown condition. The experiment consisted 16 treatment combinations comprising four varieties viz. aestivum: Raj-4079, HD-2932; durum: HI-8713, HI-8498 and four level of nutrient management viz. 100% N, P & K, 125% N, P & K, 100% N, P & K + 25 Kg ZnSO4 ha–1 and 100% N, P & K + 1% K. Combination of these treatments was evaluated under factorial randomized block design (FRBD) with three replications. Durum wheat variety HI-8713 gave highest plant height (90.5 cm), number of tillers (180.5 m–1 row), dry matter (311.6 g m–2) and flag leaf area at 50% heading (31.5 cm2) over rest of varieties. Variety HI-8713 gave maximum grain yield (5724 kg ha–1), straw yield (8073 kg ha–1), net returns (` 76582 ha–1) and B:C ratio (1.88). Variety Raj-4079 was at par with variety HD-2932 in case of net returns. Among the nutrient management, application of 125% NPK gave highest plant height, number of tillers, dry matter and flag leaf area over rest varieties. Application of 125% N, P & K recorded significantly higher grain yield (5620 kg ha–1), straw yield (8192 kg ha–1), net returns (` 76030 ha–1) and B:C ratio (1.90) over 100% N, P & K and 100% N, P & K + 25 Kg ZnSO4 ha–1. Application of 100% N, P & K + 1% K recorded significantly higher grain yield over 100% N, P & K by 6.9 per cent. 100% N, P & K + 25 Kg ZnSO4 ha–1 was at par with 100% N, P & K.